The activities of F.-W. von Bergholtz in Germany: the ways of making the collections of architectural drawings in the 18th c - Stanyukovich-Denisova, Ekaterina Yu. (Actual Problems of Theory and History of Art, 2012)
The issue deals with the yet unknown activity of F.-W. von Bergholtz, gentleman usher to the Duke of Holstein, an author of the Diary describing life at the court of Peter I. In 1730s he was an ober-hauptmann of the Kiel castle, then a tutor of the Duke Carl Peter Ulrich of Holstein. According to Y. Denisov’s and B. Hallström’s hypothesis, Bergholtz brought a collection of architectural drawings from Russia (now in the National Museum, Sweden). The author supports the hypothesis with some new facts and proposes that Bergholtz planned to commemorate sights connected with the Holstein-Gottorp dukes.
Keywords: F.-W. Bergholtz; architectural drawings; Holstein-Gottorp dukes; Tessin Hårleman Collection; Kiel castle; Björn Hallström; Yury Denisov